Tomorrow’s EFL teacher educators - González Moncada, Adriana; Quinchía Ortiz, Diana Isabel (Colombian Applied Linguistics Journal, 2003)
Teacher education programs are an important alternative to raise standards in the teaching of English as a Foreign Language (EFL). However, there are few studies that have explored the roles of teacher educators in this setting. Three main research questions guided this study: What actions have teachers taken to attain their professional objectives as EFL teachers? What experience have they had in professional development programs? What are the characteristics of an ideal teacher education program? This paper reports the findings concentrating on the ideal characteristics of an EFL teacher educator analyzing the testimonies of teachers from public and private schools. The study used four focus groups sessions and a questionnaire as the main data collection techniques. The results suggest that issues such as knowledge of local realities, broad experience in teaching EFL, command of the language, and experience in research are identified as the most desirable characteristics of EFL teacher educators.